Sol–gel synthesis of Au/N–TiO2 composite for photocatalytic reduction of Cr(vi) - Liu, Xinjuan (2013)
Au/N–TiO2 composites are successfully synthesized via a modified sol–gel method and their photocatalytic performance in reduction of Cr(VI) is investigated. Au/N–TiO2 composites exhibit an enhanced photocatalytic performance in the reduction of Cr(VI) with a maximum reduction rate of 90% under visible light irradiation as compared with pure TiO2 (34%) and N–TiO2 (80%) due to the increase of light absorption intensity and range as well as the reduction of electron–hole pair recombination in TiO2 with the incorporation of N and Au.